Feasibility and acceptability of a Whole-Body hyperthermia (WBH) protocol. (1st January 2021) - Mason, Ashley E.; Fisher, Sarah M.; Chowdhary, Anoushka; Guvva, Ekaterina; Veasna, Danou; Floyd, Erin; Fender, Sean B.; Raison, Charles
Abstract: Background: Whole-body hyperthermia (WBH) has shown promise as a non-pharmacologic treatment for major depressive disorder (MDD) in prior trials that used a medical (infrared) hyperthermia device. Further evaluation of WBH as a treatment for MDD has, however, been stymied by regulatory challenges. Objective: We examined whether a commercially available infrared sauna device without FDA-imposed limitations could produce the degree of core body temperature (101.3 °F) associated with reduced depressive symptoms in prior WBH studies. We also assessed the frequency of adverse events and the amount of time needed to achieve this core body temperature. We explored changes (pre-post WBH) in self-reported mood and affect. Methods: Twenty-five healthy adults completed a single WBH session lasting up to 110 min in a commercially available sauna dome (Curve Sauna Dome). We assessed core body temperature rectally during WBH, and mood and affect at timepoints before and after WBH. Results: All participants achieved the target core body temperature (101.3 °F). On average, it took participants 82.12 min ( SD  = 11.3) to achieve this temperature (range: 61–110 min), and WBH ended after a participant maintained 101.3 °F for two consecutive minutes. In exploratory analyses of changes in mood and affect, we found that participants evidenced reductions ( t [24] = 2.03, M diff = 1.00, p =.054, 95% CI [−2.02, 0.02]) in self-reported depression symptoms from 1 week pre- to 1 week post-WBH, and reductions ( t [24]= −2.93, M diff= −1.72, p =.007, 95% CI [−2.93, −0.51]) in self-reported negative affect pre-post-WBH session. Conclusion: This novel WBH protocol holds promise in further assessing the utility of WBH in MDD treatment. Trial registration: This trial was registered at clinicaltrivals.gov (NCT04249700).